The Dynamic Response and Characteristics of an Oxygen Vacuum Swing Adsorption Process to Step Perturbations. Part 1. Open Loop Responses - C.C.K. Beh; P.A. Webley (Adsorption Science & Technology)
Oxygen vacuum swing adsorption (VSA) has emerged as an important unit operation in many chemical engineering processes such as iron and aluminium smelting, making oxygen the third largest man-made chemical commodity in the world. Although a mature technology (with the first patents published in the 1970s), oxygen VSA processes are still not well understood due to their complicated batch-like operation, inherent non-linearities and inverse responses associated with the operating conditions. Step perturbations of manipulated variables together with the process response provide valuable information for the study of system dynamics, the extent of interaction and control loop pairings. The first part of this study presents data from input perturbations gathered from a pilot-scale experimental oxygen VSA process. The interesting time-variant temperature profiles, and bed and system pressures, flows and purity are the main focus of the discussion. Furthermore, the possible applications of this knowledge for heuristic-based control are discussed.